KARAKTERISTIK, TIPE DAN BIDANG GELINCIR PADA ZONA LONGSOR CILOTO, JAWA BARAT BERDASARKAN ESTIMASI METODE GEODETIK - Vera Sadarviana; Hasanuddin Z. Abidin; Joenil Kahar; Djoko Santoso (Pusat Survei Geologi, 2010)
Slip surface is delaminates between sliding material and undisturbed slope material. In limit equilibrium method, slip surface is used as reference for safety factor calculation. Landslides phenomenon can be observed using of GPS satellite technology to mitigation and material displacement monitoring. For that purpose, this research is carried out to estimate characteristic, type and slip surface position at Ciloto landslide zone by GPS survey.First, estimation of slip surface is carried out by slope surface profile which referred to same direction of horizontal displacement of monitored points. The same direction of horizontal displacement at several monitored points indicate that the monitored points can be located at the same slip surface. Second, maximum-minimum function of geometric method and polynomial approach, including graphical method by velocity trend line plotting for each monitored point, were done to find out point position at slip surface. Ideal planar slip surface is determined by infinite slope analysis and circular slip surface is determined by circle arc analysis. Estimation of slip surface by geodetic method approach couldn't give result because geodetic data describe slope surface. By intersection of velocity trend line of monitored point, it can gave estimation of slip surface location. Geodetic approach could gave estimation of scarp position as well as crack which is indicate beginning of slip surface. Locations of scarp in vertical profile have suitability with result of geology research at same study area.Ciloto landslide zone is classified in very slow velocity landslide (5 x 10-5 - 5 x 10-7 mm/second). The characteristic of horizontal displacement has various direction for each monitored point. Vertical displacements of monitored point have subsidence and uplift or bulging. That characteristic formed hummocky terrain and the other side of zone have gradual slope. From the research, the landslide type at Ciloto zone is multiple compound (rotational and translational) debris slides.Keywords : geodetic method, GPS survey, landslide characteristic, landslide type, slip surface, multiple landslide, scarp